HUBUNGAN MOTIVASI DENGAN PENDAPATAN PETANI CABAI MERAH YANG BERMITRA DENGAN BINAMITRA HORTIKULTURA MULTIAGROMAKMUR DI KECAMATAN AMBULU KABUPATEN JEMBER, JAWA TIMUR - Wilda Ayu Damayanti; Sri Subekti; Sudarko Sudarko (Universitas Sebelas Maret, 2017)
Chili pepper has the characteristics of rapid rot and large shrinkage that can cause production risks. Fluctuating prices of chili pepper also makes high-risk of chili pepper farming. Farmers' strategy to overcome them is to build a partnership with Binamitra Hortikultura Multiagro Makmur. Market guarantees and prices and facilities provided make farmers more motivated to cultivate chili pepper. The existence of farmer motivation in chili pepper farming is able to increase productivity so that can increase income of chili pepper farmers. The purpose of this research discusses: partnership pattern between chili’s farmers and Binamitra Multiagro Makmur, correlation between farmer’s characteristic with farmer’s motivation, and correlation between motivation with farmer income of chili pepper farmers that are partnered with Binamitra Hortikultura Multiagro Makmur Ambulu District Jember Regency, East Java. Sampling method is total sampling, that is chili pepper farmers who are partnered with Binamitra Hortikultura Multiagro Makmur with a total number of 32 farmers. Data collection was done by interview, observation, and documentation study. The research method that is used are descriptive and analytical analysis. Data analysis to determine the correlation between farmer’s characteristic with farmer’s motivation and correlation between motivation with income of chili pepper farmers uses Rank Spearman. The results were: (1) the sub-contract partnership pattern were used by farmers and Binamitra Hortikultura Multiagro Makmur, (2) there is a significant correlation between age, formal education, and cropland area with farmer motivation while the number of family dependents and experience have acorrelation that is not significant with farmer motivation, and (3) there is a significant correlation between motivation and income of chili pepper farmers.